Effect of Paraplegia on the Time Course of Exogenous Fatty Acid Incorporation Into the Plasma Triacylglycerol Pool in the Postprandial State - McMillan, David W.; Henderson, Gregory C.; Nash, Mark S.; Jacobs, Kevin A. (Frontiers in Physiology, 2021)
Spinal cord injury (SCI) results in disordered fat metabolism. Autonomic decentralization might contribute to dyslipidemia in SCI, in part by influencing the uptake of dietary fats through the gut-lymph complex. However, the neurogenic contributions to dietary fat metabolism are unknown in this population. We present a subset of results from an ongoing registered clinical trial (NCT03691532) related to dietary fat absorption. We fed a standardized (20 kcal∙kgFFM-1) liquid meal tolerance test (50% carb, 35% fat, 15% protein) that contained stable isotope lipid tracer (5 mg∙kgFFM-1 [U-13C]palmitate) to persons with and without motor complete thoracic SCI. Blood samples were collected at six postprandial time points over 400 min. Changes in dietary fatty acid incorporated into the triacylglycerol (TAG) pool ("exogenous TAG") were used as a marker of dietary fat absorption. This biomarker showed that those with paraplegia had a lower amplitude than non-injured participants at Post240 (52.4±11.0 vs. 77.5±16.0 μM), although this failed to reach statistical significance (p=.328). However, group differences in the time course of absorption were notable. The injury level was also strongly correlated with time-to-peak exogenous TAG concentration (r=-.806, p=.012), with higher injuries resulting in a slower rise in exogenous TAG. This time course documenting exogenous TAG change is the first to show a potential neurogenic alteration in SCI dietary fat absorption.